Diary Thresholds in Modern Iraqi Poetry (Journal of the College of Basic Education, 2025)
This study examines the transformations of modern Iraqi poetry by focusing on the “Daily Life Poem” as a poetic form that reflects the social, political, and cultural shifts in Iraq, especially after 2003. The research explores different poetic generations, starting from the 1950s (with Badr Shakir al-Sayyab as a model), through the 1960s (represented by Taha Hafidh and Haseb al-Sheikh Jaafar), the 1970s (Ali Jaafar al-Allaq and Jalil Haydar), and finally the 1980s (Adnan al-Sayegh). It analyzes authentic poetic texts that embody manifestations of daily life in terms of language, structure, and personal experience. The study also discusses the impact of digital media and social platforms on shaping the daily-life poem, showing how the everyday has become a central poetic theme. The research adopts a descriptive-analytical method.